ACID DEPOSITION MODELS: REQUIRED DEVELOPMENT FOR COUPLING WITH AQUATIC MODELS - Shim, Shang-gyoo (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 1993)
This paper describes the variability and uncertainty associated with dry and wet deposition, and the difficulties of using acid deposition model outputs as inputs to aquatic effects models. The necessity of developing a fast-turn-around fine grid acid deposition model will be discussed.